The crimson shard - Flavin, Teresa (Candlewick Press, 2012)
"During what seems like an ordinary museum visit, a tour guide lures Sunni and Blaise through a painted doorway-and they discover they've stepped into eighteenth-century London. When they realize their "tour guide" will do anything to get more information about what Sunni and Blaise know about magical paintings, they attempt to flee and encounter body snatchers, art thieves and forgers"--